Perancangan Kerangka Kerja Pengambilan Keputusan untuk Penilaian Kinerja Trainer menggunakan Metode Simple Additive Weighting (SAW) pada LKP Bina Karya Mandiri - Hartono, Rudi; Mualim, Imam (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The evaluation of trainer performance plays a critical role in maintaining the quality and reputation of LKP Bina Karya Mandiri as a non-formal training institution. This study aims to assess trainer performance objectively using the Simple Additive Weighting (SAW) method as part of a Decision Support Sistem (DSS). A descriptive-quantitative approach was employed through a case study involving five trainers: Wasito, Diah Rita Sari, Ahmad Jayadi, Bayu Adi Guna, and Komarudin. Data were collected through observation and surveys based on four primary criteria: Material Mastery, Teaching Methods, Participant Satisfaction, and Discipline, each assigned a predetermined weight. The findings indicate that the SAW method effectively transforms performance data into a structured and interpretable ranking. Based on preference value calculations, Bayu Adi Guna achieved the highest score of 0.935, followed by Wasito, Komarudin, Ahmad Jayadi, and Diah Rita Sari. These results demonstrate that SAW is a reliable tool for supporting decision-making in trainer performance evaluation. The implications of this study suggest that training institutions can adopt SAW to enhance objectivity, transparency, and efficiency in performance assessments, thereby strengthening human resource management practices.